ANALISIS TINGKAT KETERAMPILAN BERPIKIR KRITIS SISWA KELAS 5 SD MATA PELAJARAN IPAS - Bambang Widjajanto; Fianico Sukmana Rozy; Juwita Permata Arya Utari; Kurniasari Kurniasari; Endah Rahmawati; Julianto Julianto (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2026)
The 21st century learning paradigm demands an educational approach that emphasizes the development of high-level thinking skills, one of which is critical thinking. This skill is important to be instilled early on because it helps students analyze information, evaluate arguments, and make decisions logically. However, in reality, many elementary school students, especially grade V, still have difficulty applying critical thinking, especially in the Natural and Social Sciences (IPAS) subject. The main purpose of writing this article is to provide a deeper understanding of the level of critical thinking skills of grade V elementary school students in the Natural and Social Sciences (IPAS) subject. In addition, this article also aims to identify various factors that influence students' critical thinking skills, both from internal and external aspects of the students. The method used is descriptive qualitative research with data collection techniques through interviews, literature studies, and distributing questionnaires to students. The results of this study indicate that elementary school students' critical thinking skills in IPAS learning are still at a low to moderate level. This is indicated by students' difficulties in identifying problems, analyzing information, evaluating opinions, compiling logical arguments, understanding scientific concepts in depth, conveying structured opinions, and drawing conclusions based on evidence.